2007
DOI: 10.1385/bter:115:1:13
|View full text |Cite
|
Sign up to set email alerts
|

Weak Relationship Between Ionized and Total Magnesium in Serum of Patients Requiring Magnesium Status

Abstract: Measurement and monitoring of magnesium (Mg) are important to prevent the development of serious and potentially fatal complications in critically ill patients. Although ion-selective electrodes are available and earlier reports suggest that free ionized magnesium (iMg2+) is the most useful test to estimate Mg status, most clinical laboratories still only measure total Mg. To compare the relationship among iMg2+, total Mg, and albumin in serum, samples were collected from 48 consecutive patients admitted to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
0
26
1
Order By: Relevance
“…The later result was expected because of the fact that only 1% of Mg is found in blood and the body works very hard to keep blood levels of Mg constant [10]. However, Johansson and Whiss [55] reported that the correlation of ionized Mg (iMg2 + ) and total Mg in serum is weak. Altura et al [56] also found that short-term dietary elevations in Mg intake can result in a significant elevation of serum ionized Mg, although total serum Mg is unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…The later result was expected because of the fact that only 1% of Mg is found in blood and the body works very hard to keep blood levels of Mg constant [10]. However, Johansson and Whiss [55] reported that the correlation of ionized Mg (iMg2 + ) and total Mg in serum is weak. Altura et al [56] also found that short-term dietary elevations in Mg intake can result in a significant elevation of serum ionized Mg, although total serum Mg is unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…The pH effect on the binding of Ca and Mg to albumin and protein 14,15 has likely impacted the changes we observed and mirrored the changes in pH. Point of care devices to date for blood analyses cannot yet measure the ionized component of iMg [Abbott i-Stat ® ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between total SrMg and iMg is complex, altered in asthma and also affected by changes in serum pH. 3,8,9 Concerns about potential side effects of highdose magnesium sulfate have limited the use of this therapy outside the pharmacokinetic rationale. For example, many studies limited the maximal dose to 2000 mg, regardless of patient size.…”
Section: Introductionmentioning
confidence: 99%